Connecting a Trophic Model and Local Ecological Knowledge to Improve Fisheries Management: The Case of Gulf of Nicoya, Costa Rica - Sánchez-Jiménez, Astrid; Fujitani, Marie; MacMillan, Douglas; Schlüter, Achim; Wolff, Matthias (Frontiers in Marine Science, 2019)
Trophic models of the Ecopath with Ecosim (EwE) type and Local Ecological Knowledge (LEK), have widely been applied for fisheries assessment and management. However, there are no specific methodologies describing how (LEK) from local fishers can be incorporated with the scientific data from the models, in the context of ecosystem-based fisheries management. To our knowledge this is the first contribution exploring a systematic integration of LEK with EwE modelled output. An EwE food web model of the Nicoya Gulf ecosystem, constructed 20 years ago and recently re-visited by the authors and collaborators, was used in workshops to stimulate discussion among local stakeholders regarding changes in the marine ecosystem. For this study, 73 artisanal fishers were recruited to eight workshops. To assess the LEK the discussions were documented, and the qualitative data were analyzed with quantitative frequency of responses to identify trends. Next, we systematically compared the changes in the fishery over time through an analysis of similar, complementary and contradictory information across knowledge systems. In general, the analysis across systems reflected changes in species composition of the catches, paralleled by a harvest reduction of high trophic level species, as well as economic losses due to a shift to harvesting low value species and due to an increase in operational costs. Particularly we identified: 1) similar pieces of information that delivered the same message, providing robust evidence of changes in the social-ecological system; 2) information complementary to each other, that together provided a broader picture (descriptors and attributes) of the changes of some fishing resources; 3) conflicting pieces of information that indicated mismatches between sources of knowledge, which might suggest the cause of management problems. This study demonstrated how integrating knowledge systems can enhance our understanding of the state and changes in ecosystems, helping to improve fisheries management. We also found that an EwE model can be an effective communication tool to be used with fishers, to promote discussion and engagement. Our aspiration is to bring new and replicable tools to the policy interface in Latin-American fisheries, based on both stakeholder participation (including LEK) and the best scientific information available.